Enteric Protozoan Parasitosis and Associated Factors among Patients with and without Diabetes Mellitus in a Teaching Hospital in Ghana - Konadu, Eric; Essuman, Mainprice Akuoko; Amponsah, Angela; Agroh, Wisdom Xoese Kwadzo; Badu-Boateng, Ernest; Gbedema, Stephen Yao; Boakye, Yaw Duah (International Journal of Microbiology, 2023)
Background. Enteric protozoa infections (EPIs) could worsen clinical outcomes in patients with diabetes mellitus and therefore requires prompt and accurate diagnosis and attention. This study aimed to determine the burden of EPIs and their associated factors among patients with and without diabetics at the Komfo Anokye Teaching Hospital (KATH) in Ghana. Again, the diagnostic performance of parasitological techniques routinely used for diagnosis was assessed. Methods. A total of 240 participants (made up of 140 patients with diabetes and 100 patients without diabetes) were recruited into the study by simple random sampling from November 2020 to May 2021. Stool samples of participants were collected, along with their demographic information, and examined using the saline direct wet mount (DWM), formol-ether concentration (FEC), and modified Ziehl–Neelsen staining (ZNS) techniques for the presence of enteric protozoans. Results. Enteric protozoa were found among 62/140 (44.3%) diabetic patients and 13/100 (13.0%) nondiabetic patients. The predominant protozoa identified were Cryptosporidium spp. (17.86%) among patients with diabetes and Blastocystis hominis (7.0%) among patients without diabetes. EPI was associated with diabetes mellitus status (AOR = 3.48, 95% CI, 1.55–7.79), having diabetes for more than five years (AOR = 3.83, 95% CI, 1.65–8.86) and having comorbidity (AOR = 2.93, 95% CI, 1.33–6.45). The FEC technique had the highest sensitivity (100.0%), specificity 94.3% (95% CI, 91.35–97.22), and accuracy 95.0% (95% CI, 88.54–98.13) when compared to other techniques for diagnosis. Conclusion. EPIs are a significant health problem among patients with diabetes at KATH, and therefore antiparasitic drugs should be included in their treatment protocols for better health outcomes. Again, the FEC technique has demonstrated better performance in detecting EPIs and is therefore recommended to achieve early and accurate diagnosis of EPIs.